Annual educational bibliography of the international bureau of education, 1958 - International Bureau Of Education, Geneva (Switzerland).; International Bureau of Education, Geneva (Switzerland). (Washington, D.C. : ERIC Clearinghouse, 1959)
This annual educational bibliography is an annotated catalog of about 1,000 of the chief educational publications incorporated in the international education library during 1964. The areas covered are--(1) generalities, (2) theory and education, (3) general aspects of education covering such fundamental types of education as the teaching staff, school organization, intellectual education, systems of education, discipline, school buildings, school hygiene, the pupil, and special education, (4) primary education, (5) secondary education, (6) adult education, (7) special didactics, (8) education according to sex and age, (9) education of the personality, (10) higher education, (11) school administration, and (12) related topics, which include psychoanalysis, child and adolescent psychology, psychiatry, and television. An alphabetical author index is included. (ha)
Educational level discussed: Adult Education.
Educational level discussed: Higher Education.
Educational level discussed: Primary Education.
Educational level discussed: Secondary Education.
Microfiche.
Keywords: Adult Education; INTERNATIONAL EDUCATIONAL LIBRARY -- SWITZERLAND -- Switzerland (Geneva)